The diverse benefits of biodiversity conservation in global ocean areas beyond national jurisdiction - Santos, Bianca S.; Devereaux, Sabrina G.; Gjerde, Kristina; Chand, Kevin; Martinez, Janet; Crowder, Larry B. (Frontiers in Marine Science, 2022)
The end of the long and winding road towards a milestone new treaty focused on the conservation and sustainable use of marine biodiversity beyond national jurisdiction (BBNJ) is near. The BBNJ treaty has the potential to dramatically transform environmental stewardship in the high seas, making it essential that vigorous support towards a strong treaty continues, without weakening the agreement’s full potential. Historically, the dialogue surrounding the BBNJ negotiations has focused on the agreement’s environmental and conservation-related impacts. Here, we begin to highlight the many diplomatic, economic, and social benefits of a vigorous and equitable BBNJ treaty. We found that strong support for the BBNJ treaty could strengthen multilateral institutions and bolster international cooperation towards common environmental goals. It could also enhance the health of shared marine ecosystems and resources and drive truly sustainable ocean-based economic growth. Finally, the treaty has the potential to engage equity as a key principle, to begin tackling global ocean inequalities in a meaningful way. Together, we find that the new treaty has the potential for widespread and diverse benefits for all member nations. It is past time for the international community to address the global governance gap in the high seas in an ambitious and equitable manner.